Thermal and Mechanical Properties of Vinyl Ester Hybrid Composites with Carbon Black and Glass Reinforcement. (21st September 2021) - Guggari, Geetanjali S.; Shivakumar, S.; Manjunath, G. A.; Nikhil, R.; Karthick, Alagar; Edacherian, Abhilash; Ahamed Saleel, C.; Afzal, Asif; Prasath, S.; Saleh, B.
Abstract : The objective of the work is to investigate both thermal and mechanical properties of vinyl ester/glass composites incorporated with different percentages of carbon black reinforcements through experimental approaches. Analysis of glass transition temperature, thermogravimetric analysis (TGA), degradation temperature, hardness, flexural strength, etc. is performed using differential scanning calorimeter, X-ray diffraction, tensile machine, and flexural machine, respectively. The scanning electron microscope was used for surface fracture studies. The degradation temperature reduces initially with the percentage of carbon black and then increases. Glass transition temperature increases with the percentage of carbon black while above 500°C temperature, the weight percentage of composite drops. The results also reveal that 4% of carbon with vinyl ester improved the tensile strength by 30%, hardness by 35%, flexural strength by 45%, flexural modulus by 66%, and interlaminate shear strength by 44% when compared with the other percentage of carbon black.